High Risk of Metabolic Dysfunction in Nonobese Breast Cancer Survivors - da Silva-Filho, Pedro Paulo P. [UNESP]; Buttros, Daniel A.B. [UNESP]; Buttros, Luciana A.B. [UNESP]; Esperança, Giulliano [UNESP]; Gubolino, Pedro Luiz F. [UNESP]; Carvalho-Pessoa, Eduardo [UNESP]; Vespoli, Heloisa D.L [UNESP]; Nahas, Eliana A.P. [UNESP] (Elsevier, 2025)
Background: The aim of this study was to evaluate the metabolic profile of non-obese postmenopausal women with breast cancer (BC) compared to non-obese women without breast cancer. Methods: In this case-control study, 130 women with BC, aged 45–75years, body mass index < 30kg/m2 and without established cardiovascular disease were included. The control group consisted of 130 women with the same inclusion criteria, but without BC. The groups were matched by age and time since menopause. Clinical, anthropometric, and biochemical data were collected. Women who presented three or more diagnostic criteria were considered to have metabolic syndrome (MetS): waist circunference > 88cm; triglycerides ≥ 150mg/dL; HDL-cholesterol < 50mg/dL; blood pressure (BP) ≥ 130/85mmHg; glucose ≥ 100mg/dL. Results: Women with BC had a higher occurrence of MetS and elevated BP compared to the control (30.8% vs. 20.0% and 25.4% vs. 14.6%, respectively) (P < 0.05). A higher percentage of women with BC had values above the desirable range for total cholesterol and glucose compared to the control (56.2% vs. 43.1% and 29.2% vs. 15.4%, respectively) (P < 0.05). In the risk analysis of the metabolic profile, adjusted for age and menopausal status, women with BC had a significantly higher risk for MetS (OR =%2.76, 95% CI 1.48-5.15), elevated glucose (OR = 2.69, 95% CI 1.46-4.96), and hypertension (OR = 3.03, 95% CI 1.51-6.10). Conclusion: Non-obese women with BC had a higher risk for MetS, hypertension, and diabetes, with a worse metabolic profile compared to non-obese women without BC. Prospective studies are needed to validate our results.
Keywords: Diabetes; Hypertension; Menopause; Metabolic syndrome; Obesity